Attenuation of Morphine Physical Dependence and Blood Levels of Cortisol by Central and Systemic Administration of Ramelteon in Rat - Majid Motaghinejad; Ozra Motaghinejad; Pantea Hosseini (Iranian Journal of Medical Sciences, 2015)
Background: Chronic administration of morphine cause physical dependence but the exact mechanism of this phenomenon remains unclear. The aim of this study is the assessment of systemic and intracerebroventricular (icv) administration of ramelteon (a melatonin receptor agonist) on morphine physical dependence. Methods: 88 adult male rats were divided into 2 major groups, namely “systematic” and “central” administration of ramelteon. In the first category, systemic administration of ramelteon at various dosages (10, 20, and 40 mg/kg) was assessed on dependent animals and withdrawal signs were compared with positive (received morphine and saline as systemic administration), negative control (saline) and group under treatment by ramelteon (40 mg/kg) groups. In the second category, central administration of ramelteon at various dosages (25, 50, or 100 μg,) was assessed on dependent animals and withdrawal signs were compared with the positive control (received morphine and saline as icv) and negative control (saline) groups, and the group under treatment by ramelteon (50 μg/5 μl/rat). On the test day, all animals received naloxone (3 mg/kg) and were observed for withdrawal signs. Total withdrawal score (TWS) was also determined. Finally, to evaluate the stress level of dependent rats, blood cortisols were measured. Results: Central administration of ramelteon in all doses and systemic administration in high doses attenuate withdrawal syndrome in comparison with the dependent positive control group (P<0.05). Both central and systemic administrations of ramelteon can attenuate the blood cortisol level in comparison with the dependent positive control group (P<0.05). Conclusion: In conclusion, we found that central administration of ramelteon attenuated morphine withdrawal symptoms and cortisol level as a stress marker.